Wordsworth's theory of education - Finley, Josephine (My University, 1900)
Introduction: The Scottish author and critic, Dr. Moir, says of Wordsworth, “Never, perhaps, in the whole range of history, from Homer downwards, did any individual, throughout the course of a long life, dedicate himself to the poetry with a devotion so pure, so perfect, so uninterrupted as he did. It was not his recreation, his mere pleasure, it was the main, the serious the solemn business of his being. It was his morning, noon and evening thought, the object of his outdoor rambles, the subject of his indoor reflections, and as an art he studied it as severely as ever Canova did sculpture, or Michael Angelo painting.” He was a master of his art, giving to the world his message of love of Nature, God and Man through the realm of beautiful verse. Poetry was the channel through which the stream of noble thoughts and sentiments flowed from the still, placid waters of his own deep mind to the generation of today. Wordsworth speaks of poetry as “the impassioned expression which is in the countenance of all science,” and ad “the breath and finer spirit of all knowledge.” Keats, beautiful and impassioned poet as he was scorned the idea that a poem should bear a lesson. To him, poetry was but the expression of sensuous beauty. Wordsworth claims that the poets function is to “Help life onward in its noblest aim.” He tells us that his purpose was “to teach the young of every age to see, to think, and therefore to become more securely virtuous.” Writing to Sir George Beaumont he says, “The poet is a teacher. I wish to be considered as a teacher or as nothing.”
Citation: Finley, Josephine. Wordsworth's theory of education. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Wordsworth; Education; Poetry; Theses; Manuscripts (documents)